A REPRESENTAÇÃO DISCURSIVA DA ESCRAVIDÃO NO BRASIL EM VIDEOAULAS DE HISTÓRIA - Saraiva, Gabriela Luz (2020)
As a very wide area of knowledge, History involves the study of pertinent topics to the society and also the relations of power, work, representations, and discourses that permeate these historical processes. From a historiographical perspective, slavery arises as a worldwide, historical, social, and political phenomenon that has been and still is present in many ways in the history of mankind. Therefore, we noticed the necessity to investigate how slavery is discursively represented in online classes from YouTube to the subject of History of Brazil, studied in High School. To this end, we analyzed of the online class “A escravidão no Brasil (ou a maior cicatriz do Brasil)”, from the points of view of discourse analysis and historiography. From the analysis, we realized that the theme of slavery, in the video class, is presented as a consequence of contextual factors of that era. We also realized that this topic does not receive appropriate critical treatment, and is approached as a fact situated in the colonial history of the country.